other side of an airport’s two-sided market: issues in planning and pricing airport surface access - Kenneth Button (European Journal of Transport and Infrastructure Research, 2017)
The first part of the paper considers the two-sided nature of airport platforms, and argues that on the land-side, analysis and policy has generally over-stated the items that should be included. In this context, the paper’s focus is on airport access and how it should be embraced, along with airside considerations, in a two-sided framework when establishing prices and investment. In the second part, the more theoretical argument is juxta positioned with prior empirical analysis of landside access which has largely been treated in a rather ad hoc way, usually implicitly assuming it involves a one-sided market. The subsequent arguments of what needs to be done, are suggestive rather than specific given the diverse institutional and physical nature of airports and their surroundings.